(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2023)
The article focuses on Leibniz’s theory of dual access to the innate practical truths developed in the New Essays, on the background of the reconciliation between egoism and altruism he pursues – since his early writings on natural law – through the categories of disinterested love and charity, and the onto-aesthetic implication between harmony and pleasure as well. After reconstructing the meaning and the functions of the argument on the community of brigands that Leibniz addresses against Locke’s conventionalism, the article dwells on the structure of social instincts in human and non-human animals and emphasises the role of the “prick of conscience”, conceived of as a first, affective and pre-rational step in the construction of otherness.